Upaya Peningkatan Hasil Belajar Siswa Kelas 1 SD Negeri Pudakpayung 01 Menggunakan Model Pembelajaran Teams Games Tournament (TGT) Tahun Ajaran Gasal 2021/2022 - Maria Ulfa (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Indonesian is one of the mandatory subjects which is expected to develop students' abilities, namely: (1) listening (listening skills); (b) speaking (speaking skills); (c) reading (reading skills); and (d) writing (writing skills). The aim of this research is to improve the learning outcomes of grade 1 students at SD Negeri Pudakpayung 01 Using the Teams Games Tournament (TGT) Learning Model for the 2021/2022 Odd Academic Year. This research method is Classroom Action Research (PTK) with four stages in each cycle. The results of this research are an increase in learning outcomes in Indonesian language subjects for grade 1 students at SD N Pudakpayung 01 Odd School Year 2021/2022 using the TGT cooperative learning model. The increase from cycle I where 19 students completed the test with a percentage of 65.52% became 26 students with a percentage of 89.66% in cycle II.